Refractory concretes bonded with calcium aluminate phosphate (CAP) mechano-chemical binder - Nagorniy, Andriy (F. A. Finger – Institut für Baustoffkunde, Deutschland, 2018)
The present paper identifies the phosphate phases responsible for developing proper mechanical-strength properties of alumina concretes bonded with mechano-chemical binders. It sets out the colloid and crystalline phases resulted from interphase interaction that provide the basis for high concentrated bonding suspensions (HCBS) technology useful to the refractory industry. The concretes obtained retain their volume integrity after 30 cycles of heating and cooling; can be used for refractory applications 1700 °С; exhibit sufficient strength of lining 40 MPa.

У статті висвітлюються фосфатовмісні фази, що є відповідальними за необхідні фізико-механічні властивості високоглиноземних бетонів на механо-хімічному в’яжучому. Встановлено, що колоїдні та кристалічні фази, утворені внаслідок міжфазної взаємодії, забезпечують підґрунтя для застосування висококонцентрованих в’яжучих суспензій (ВКВС) у вогнетривкій промисловості. Отримані бетони демонструють об’ємосталість, термостійкість понад 30 теплозмін, експлуатаційну міцність 40 МПа та вогнетривкість 1700 °С.
Keywords: refractory concrete; mechano-chemical binder; thermal-shock resistance; aggregate; вогнетривкий бетон; механо-хімічне в'яжуче; термостійкість; заповнювач